Comparison of factor of safety using different method of analysis for slope stability - Ahmad Amirul, Mohd Zaki (2015)
Slope failure in our country is an issue that needs to be taken seriously as it involves public safety. Therefore there are various efforts being carried out, particularly in the treatment of critical slope, redesign the slope that has failed and also analyze the factor of safety of the slope. This study was conducted to determine the safety factor of the slope at KM259.95 the North-South Expressway which is cut slope that built for infrastructure development, using computer software, Geo-studio 2007 (SLOPE / W) and the conventional method; infinite slope method in sand. Based on site investigation report, the slope has sandy soil profile. The first layer is silt with properties γ= 18.25kN/m3, c’ = 0kN/m, ϕ’ = 39o, sand with properties γ= 16.19kN/m3, c’ = 0kN/m2 ϕ’ = 39o and granite (impermeable) .To carry out this analysis, three cross-sections have been developed to obtain the factor of safety. Using all the parameters, the factor of safety has been obtained for the three cross sections. Using conventional method, the factor of safety (FOS) for cross section A, cross section B and cross section C is 1.036, 1.000 and 1.036 respectively. While for the FOS for cross section A using SLOPE/W for Morgenstern Price, Janbu’s, Ordinary and Bishop are 1.156, 1.091, 1.090 and 1.135 respectively. For the cross section B, the FOS for Morgenstern Price, Janbu’s, Ordinary and Bishop are 1.509, 1.283, 1.303 and 1.392 respectively. And for cross section C, the FOS for Morgenstern Price, Janbu’s, Ordinary and Bishop are 1.284, 1.250, 1.251 and 1.300 respectively. After obtaining the factor of safety for the slope, the coefficient for each type of analysis has been evaluated. For all cross section, the coefficient for Morgenstern Price analysis is 0.789, Janbu’s method with 0.853, Ordinary method with 0.848 and Bishop Method with 0.809. The percentage difference between the factor of safety for SLOPE/W and conventional has also analyzed where Morgenstern Price method has the highest difference of 0.211% and the lowest percentage of different between both methods is Janbu’s method with 0.147%. For the Ordinary and the Bishop method, the percentage difference is 0.152% and 0.191%.As a conclusion, factor of safety for cut slope of research is critical and requires immediate treatment with appropriate improvements. From percentage difference, both methods still suitable to be used as a way to get the optimum safety factor of slope.